1995
DOI: 10.1055/s-0038-1653753
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Factor VIII Inhibitor Development in Severe Hemophilia A Patients Treated only with One Brand of Highly Purified Plasma-Derived Concentrate

Abstract: SummaryThe incidence of factor VIII inhibitor was studied in a cohort of 56 previously untreated patients with severe hemophilia A (factor VIII below 1 U/dl). They received only one brand of highly purified factor VIII concentrate (HPSD-VIII) prepared by conventional chromatography with a solvent-detergent step for viral inactivation. Followup since the first infusion of HPSD-VIII was from 1 to 76 months (mean = 29) and cumulative exposure days (CED) from 1 to over 100 (median = 26). Five patients (9%) develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 6 publications
1
42
0
Order By: Relevance
“…The first cohort was treated with a French plasma-derived concentrate (FVIII-LFB) 16 and the second with full-length recombinant factor VIII. 22 The aim of this work was to compare the incidence of FVIII inhibitors in these two cohorts, independently of all other recorded risk factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first cohort was treated with a French plasma-derived concentrate (FVIII-LFB) 16 and the second with full-length recombinant factor VIII. 22 The aim of this work was to compare the incidence of FVIII inhibitors in these two cohorts, independently of all other recorded risk factors.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of the type of FVIII concentrate in PUPs with severe hemophilia A is highly controversial. 14,15 A low incidence of inhibitors (0%-11%) was observed in patients treated only with some plasma-derived FVIII concentrates in some studies, [16][17][18] contrasting with an incidence of 24% to 33% in the first international prospective studies of recombinant factor VIII. [19][20][21] To determine whether the incidence of inhibitors is indeed higher in PUPs with severe hemophilia A treated with recombinant FVIII, we reanalyzed individual data from 2 retrospective studies involving PUPs with severe hemophilia A who were treated with either a plasma-derived FVIII concentrate 16 or a recombinant FVIII concentrate.…”
Section: Introductionmentioning
confidence: 99%
“…This review evaluated the role of the different FVIII products on the risk of inhibitor development. The cumulative risk in PUPs was reported to range from 0 [51] to 12.4% [52] for patients treated with a single plasma-derived concentrate, to 36.0 [53] to 38.7% [54] for patients treated with a single recombinant product. Studies published thereafter have shown that in patients treated with a 2nd generation rFVIII products the incidence of inhibitors was ranging from 16.7% to 32% [55,56].…”
Section: Plasma Derived Vs Recombinant Concentrates Safetymentioning
confidence: 99%
“…[26][27][28] A systematic review by Wight and Paisley 29 also supports the views that the source of FVIII may influence inhibitor development. A disparate cumulative incidence of inhibitors between plasma-derived (0%-12%) 30,31 and recombinant FVIII products (36%-38.7%) 32,33 was found in PUPs. 29 These results were received with some skepticism by the hemophilia community because the studies included in the analysis were very heterogeneous with regards to size, design, population, inhibitor definition, and also inhibitor incidence (Figure 1).…”
Section: Introductionmentioning
confidence: 98%